The case of national health promotion policy in Australia: Where to now? - Smith, J.; Crawford, Gemma; Signal, L. (Australian Health Promotion Association, 2016)
Issue addressed Over the last three decades there has been an incremental investment in health promotion and prevention across Australia; yet, the Commonwealth Government and some state/territory governments have more recently instigated funding cuts in health promotion and prevention. This paper argues that the role of health promotion is critical in contemporary Australia and discusses strategies needed to move forward within the context of recent disinvestments. Discussion Key areas of concern relating to recent health promotion and prevention disinvestment in Australia include the abolishment of the Australian National Preventive Health Agency, the cessation of the National Partnership Agreement on Preventive Health and significant cuts to Indigenous programs. These changes pose a significant threat to the health, economic and social well being of Australians and the region, particularly those that are most vulnerable. Conclusions Future health promotion and prevention efforts will require strategic leadership and action to enhance the promotion of health equity in Australia over the coming decades. We call on governments to (re)invest in health promotion and prevention both in and outside the health sector so that health promotion professionals can continue their advocacy efforts aimed at articulating their professional place in improving population health. So what? Recent changes to national health promotion and prevention policy are detrimental to the health and well being of the Australian population, particularly those most vulnerable. Sound planning to revitalise and refocus health promotion action in Australia is urgently required.